Peranan Hukum Ekonomi Islam dalam Meningkatkan Kesejahteraan UMKM di Indonesia - Aryani, Katrin; Masturah, Dienna; Latifa W, Asisha; Dilaga, Irsyan Satria; Ilmiyawan, Khairul Rizal; Siswajanthy, Farahdinny (Indonesian Journal of Law and Justice, 2023)
Micro, Small and Medium Enterprises (MSMEs) is an economic sector that plays an important role in improving the welfare of the people in Indonesia. However, MSMEs still face various obstacles, one of which is the legal aspect. This research aims to examine the role of Islamic economic law in improving the welfare of MSMEs in Indonesia. The research method used is qualitative, using literature studies and interviews with several Islamic MSME actors. The results show that Islamic economic law has a positive role in improving the welfare of MSMEs, both in terms of economic, social, and spiritual aspects. Islamic economic law provides principles that are in accordance with Islamic values, such as justice, balance, transparency, accountability, and social responsibility. Islamic economic law also provides legal protection for MSMEs, both in terms of licensing, agreements, and dispute resolution. Thus, Islamic economic law can be one of the solutions to overcome the problems of MSMEs and improve the welfare of the people in Indonesia.